Differential Contribution of Skeletal and Cardiac II-III Loop Sequences to the Assembly of Dihydropyridine-Receptor Arrays in Skeletal Muscle - Takekura, Hiroaki (The American Society for Cell Biology, 2004)
The plasmalemmal dihydropyridine receptor (DHPR) is the voltage sensor in skeletal muscle excitation-contraction (e-c) coupling. It activates calcium release from the sarcoplasmic reticulum via protein–protein interactions with the ryanodine receptor (RyR). To enable this interaction, DHPRs are arranged in arrays of tetrads opposite RyRs. In the DHPR α(1S) subunit, the cytoplasmic loop connecting repeats II and III is a major determinant of skeletal-type e-c coupling. Whether the essential II-III loop sequence (L720-L764) also determines the skeletal-specific arrangement of DHPRs was examined in dysgenic (α(1S)-null) myotubes reconstituted with distinct α(1) subunit isoforms and II-III loop chimeras. Parallel immunofluorescence and freeze-fracture analysis showed that α(1S) and chimeras containing L720-L764, all of which restored skeletal-type e-c coupling, displayed the skeletal arrangement of DHPRs in arrays of tetrads. Conversely, α(1C) and those chimeras with a cardiac II-III loop and cardiac e-c coupling properties were targeted into junctional membranes but failed to form tetrads. However, an α(1S)-based chimera with the heterologous Musca II-III loop produced tetrads but did not reconstitute skeletal muscle e-c coupling. These findings suggest an inhibitory role in tetrad formation of the cardiac II-III loop and that the organization of DHPRs in tetrads vis-à-vis the RyR is necessary but not sufficient for skeletal-type e-c coupling.